Small Cell Lymphocytic Lymphoma: An Unexpected Etiology of Pleural Effusion - Silva, Filipa; Ramos, Sara; Pereira, Carla; Mesquita, Pedro; Teixeira, João; Correia, Maria; Sena, Pedro; Duarte, Joana; Araújo, Inês; Fonseca, Cândida (International Journal of Innovative Research in Medical Science, 2021)
The differential diagnosis of pleural effusion is extensive. Pleural fluid characteristics are helpful in classifying, as transudate or exudate, being this determinant to achieve an accurate diagnosis. The authors present a clinical report of a 74-year-old man with reduced left ventricular ejection fraction heart failure, of ischemic etiology, and multiple cardiovascular risk factors, who develops a pleural effusion. In his medical history it is important to denote a recent diagnosis of colon adenocarcinoma, without evidence of metastatic disease, submitted to hemicolectomy. Four months after this diagnosis, he was admitted in the Emergency Department with dyspnea, type 1 respiratory failure and de novo pleural effusion. The most probable etiologies of pleural effusion were excluded, including heart failure and a metastatic disease. Ultimately, it was reported a difficult (or not so) and unexpected etiology for the pleural effusion, in a patient with multimorbidity and multiple confounders. It is crucial to see beyond the obvious. A real-life challenge for Internal Medicine.